Mechanisms of foreign language learning anxiety and enhancement strategies among Chinese tertiary students: a grounded theory approach - Junxia Gao; Yanpeng Zuo (Frontiers in Psychology)
Given the dynamic and contextual nature of foreign language learning anxiety (FLLA) and its impact on language acquisition, this study aims to gain a deeper understanding of the factors and mechanisms that underlie FLLA. Utilizing Nvivo 12 and grounded theory, the study conducts a coding analysis of interview data from tertiary students from 16 higher institutions in China, and reflection journals from two classes at a vocational college in China. The analysis identifies two core categories of anxiety: external sociocultural factors and internal self-regulation issues. The study constructs a model which indicates that external factors, such as maladaptation to the academic transition, disconnection between high school and university curricula, and intense academic competition, directly contribute to this anxiety. Intense academic competition raises students’ self-expectations, exacerbates time management difficulties, and further intensifies their anxiety. Additionally, a vicious cycle develops between students’ foreign language learning anxiety and their internal motivation and self-efficacy. To alleviate this anxiety, the study proposes teaching strategies to foster positive emotions, including enhancing self-regulation, instilling a growth mindset, promoting flow experiences, cultivating a positive self-concept, and creating a supportive classroom atmosphere. Future research should adopt a dynamic complexity theory perspective to explore trends in anxiety and its relationships with other affective factors, with the goal of developing more effective interventions.